Evaluation of Newborns Born in a Training and Research Hospital in Mogadishu,Somalia, Africa - Cüneyt Uğur; Abdisalam Abdullahi Yusuf (Mashhad University of Medical Sciences, 2020)
Background: This study aimed to determine the clinical characteristics of the newborns born in the hospital. Methods: This study included 1199 newborns born in Turkey Recep Tayyip Erdoğan Training and Research Hospital, Mogadishu, Somalia, Africa, in 2018. The gender, birth weight and height, delivery method, health status, mother's age, as well as gravida and parity conditions were retrospectively obtained from the records of the delivery clinic. Results: Out of 1199 newborns, 610 neonates were male (50.9%). The mean birth weight of the newborns was 2915.7±907.5 gr, and the mean birth height was 47.6±4.6 cm. Moreover, 66.6% of the newborns were born by normal vaginal delivery, and 91.8% were born alive. The mean age of the mothers was 26.3±5.4 years, and the mean values of gravida and parity were 3.8±2.5 and 2.9±2.1, respectively. Conclusion: There is a dearth of research regarding the evaluation of newborns in Somalia, Africa. Therefore, it is hoped that the results of this study will contribute to form standards for the follow-up of growth and development of infants living in this region and to improvematernal and child health.